Dynamic interaction between heavy-haul train and track structure due to increasing axle load. Issue 3 (3rd July 2017) - Zhang, Dawei; Zhai, Wanming; Wang, Kaiyun
Abstract: This paper aims to investigate dynamic interaction between heavy-haul train and track structure with emphasis on the influence of the increasing axle load. A three-dimensional heavy-haul vehicle–track coupled dynamics model is developed, in which a typical freight vehicle with three-piece bogies is modelled as a 47-degree-of-freedom multi-body system. The realistic track irregularity data collected in a heavy-haul railway are expressed as track spectra in the form of the exponential functions, and the inversed track irregularities acting as system excitations are input into the theoretical simulation. A full-scale field test is then carried out to measure the dynamic responses of the coupled system excited by moving trains, and the measured results well validate the proposed model. By means of the validated model, the effect of the increasing axle load on the dynamic behaviour of the vehicle–track coupled system is investigated. Results indicate that the increasing axle load intensifies the vertical wheel–rail force and rail–sleeper force obviously, but the wheel unloading rate and derailment coefficient display an opposite tendency. Meanwhile, the increasing axle load exacerbates the stress in the track and thickening the ballast can effectively decrease maximum pressure on subgrade surface.